Association between suicidal ideation and cognitive function in young patients with schizophrenia spectrum disorder - Kim, Ji-Su; Baek, Seon-Hwa; Kim, Honey; Kim, Ju-Wan; Kang, Hee-Ju; Ryu, Seunghyong; Lee, Ju-Yeon; Kim, Jae-Min; Kim, Sung-Wan (Frontiers in Psychiatry, 2023)
Introduction Suicide is a major concern for patients with recent-onset schizophrenia. We hypothesized that preserved cognitive function might be associated with a higher level of suicidality in patients with schizophrenia. We investigated the associations between cognitive function and suicidal ideation (SI) in young patients recently diagnosed with a psychotic disorder. Methods This study analyzed data from a naturalistic clinical cohort study that comprised 402 patients with schizophrenia spectrum disorder. Patients with a treatment duration of ≤5 years and an age range of 15–39 years were enrolled. Participants were categorized into two groups based on SI as assessed by the Columbia Suicidal Severity Rating Scale. We collected demographic and clinical data and administered psychiatric, neurocognitive, and social cognitive measures. Results Among participants, 52% reported experiencing SI. Patients with SI were significantly younger and had a longer duration of untreated psychosis (DUP) than those without it. The Positive and Negative Syndrome Scale-general psychopathology score was significantly higher in the SI group. Scores on the Calgary Depression Scale for Schizophrenia, Perceived Stress Scale, Beck Depression Inventory (BDI), and Beck Hopelessness Scale were significantly higher among patients with SI, while scores on the Subjective Well-being Under Neuroleptics-Short Form and Brief Resilience Scale were significantly lower compared to those without it. Patients with SI demonstrated significantly higher scores on the verbal and visual learning test, false belief task, picture stories task, and Controlled Oral Word Association Test. They also completed the Trail Making Test (TMT) parts A and B in significantly less time than those without it. After adjusting for age, DUP, and scores on the BDI, group differences in scores on the verbal and visual learning tests, TMT (parts A and B), and the false belief task, and the picture story task remained significant. Discussion Our results suggest that along with traditional risk factors, better cognitive function may also be a major risk factor for suicidality in patients with schizophrenia. Providing psychological support and cognitive interventions is essential for young patients with recent-onset schizophrenia spectrum disorders, particularly those with high levels of depression, hopelessness, perceived stress, low resilience, and good cognitive function.